Pengaruh Model Pembelajaran Problem Based Learning (PBL) dan Jigsaw Terhadap Hasil Belajar Matematika Ditinjau Dari Motivasi Belajar Siswa (Penelitian Eksperimen Kelas VII Semester Gasal Di MTs Negeri Surakarta II Tahun Ajaran 2015/2016) - Rahmawati, Vema (2016)
The purposes of the research are to describe and analysis of: (1) The influence of mathematic with a Problem Based Learning and Jigsaw model toward result of mathematic lesson. (2) The influence of students' study motivation toward the result of mathematic lesson. (3) The interaction between model and students' study motivation toward mathematic result. The design of the research used in Quasi Experimental Design. The population in this research are two classes. The sampling of this research are all of the seventh classes in the odd semester of MTs N Surakarta 2 academic year 2015/2016. The samples of this research is cluster random sampling. The method of collect the data used test and documentation. The technique of data analysis used two stripes with a different cells. The result of the significant degree 5% providable (1) there is Jigsaw toward result of mathematic with . There is a students' study motivation toward the result of mathematic lesson with . (3) there are not interaction bethwen Jigsaw model and Problem Based Learning model looked at students' study motivation toward the result of mathematic lesson with